The Electrolytic Production of Rare Earths from Their Oxides - James C. Withers (The Minerals, Metals and Materials Society, 2018)
There is no production of rare earth metals in the U.S. in spite that the U.S. is the largest consumer of rare earths in some form that includes consumer and Department of Defense (DoD) devices. The one U.S. mine has been purchased by the Chinese that even enhances their monopoly on rare earths. A research effort has demonstrated rare earth oxides can be extracted from bastnaesite ore as well as coal ash at efficiencies in the upper 90s percent. The rare earth oxide can be carbothermically treated to produce an oxycarbide which is highly electrically conductive. The rare earth oxycarbide can be used as an anode in anhydrous fused salts electrolysis to produce a highly purified rare earth powdered metal. It is also possible to electrofractionate the individual metals which can be combined with co-deposition of iron and boron to produce the highly magnetic alloy Nd2Fe14B.